Charisma attribution during organizational change: the importance of followers' emotions and concern for well‐being. Issue 6 (22nd May 2013) - Chen, Chao C.; Belkin, Liuba Y.; McNamee, Robert; Kurtzberg, Terri R.
Abstract Taking a follower‐centric perspective, we examined how charisma attribution to a change leader was influenced by the well‐being concerns and emotions of organizational members. We conducted three studies to examine how college business students and Executive Master of Business Administration (EMBA) students responded to a grading policy reform aimed at reducing grade inflation. We found that emotions and well‐being concerns such as school year and grade point average influenced charisma attribution by the undergraduate students and that there was a greater divergence of emotional reactions and charisma attribution among undergraduate students than among the executive MBAs. Future directions for follower‐centric leadership research on charismatic leadership are discussed.